Epidemiological and clinical impact of hepatitis E virus coinfection in chronic hepatitis B infected patients in Hebei, China - Shi, Yuzhu; Xie, Yuchen; Chen, Ying; Yang, Li; Gao, Huixia; Guo, Yun; Feng, Fumin; Lu, Jianhua; Dai, Erhei (Frontiers in Microbiology, 2025)
IntroductionHepatitis B virus (HBV) infection poses a major global public health challenge. Recent studies have highlighted the clinical implications of coinfection with the hepatitis E virus (HEV) in HBV-infected individuals, as this dual infection is associated with exacerbated disease severity. However, epidemiological data on HBV/HEV coinfection in the Hebei region are scarce, necessitating further investigation.MethodsWe conducted a multicenter cross-sectional study for infectious diseases across six tertiary hospitals. Serum samples were screened for anti-HEV IgM and IgG antibodies by using an automated chemiluminescent immunoassay. Samples positive for anti-HEV antibodies were further subjected to HEV RNA detection using the reverse transcription polymerase chain reaction (RT-PCR). The seroprevalence of anti-HEV antibodies was 18.70% (582/3,113).ResultsAmong these, 562 cases were positive for anti-HEV IgG, 4 were positive for anti-HEV IgM, and 16 were positive for both anti-HEV IgG and IgM. HEV RNA was detected in 16 (2.75%; 582) anti-HEV-seropositive individuals. A strong positive correlation was observed between anti-HEV seroprevalence and advancing age [R2 = 0.966 in the liver cirrhosis (LC) group, R2 = 0.774 in the hepatocellular carcinoma (HCC) group, and R2 = 0.508 in the chronic hepatitis B (CHB) group]. Multivariate analysis confirmed that older age was an independent risk factor for anti-HEV seropositivity (OR = 1.03, 95% CI: 1.02–1.04, P < 0.001). HBV mono-infection patients were significantly younger than those with HBV and acute HEV coinfection patients or HBV with previous HEV infection patients (53.0 vs. 58.5 vs. 58.0 years, P < 0.001). Additionally, LC and HCC were more prevalent in the HBV with previous HEV infection than in HBV mono-infection (65.98% vs. 77.27%, P < 0.001). Compared to HBV mono-infection patients, the activated partial thromboplastin time was significantly prolonged in both HBV and HEV acute coinfection patients and in those with HBV and previous HEV infection (32.30 s vs. 35.65 s vs. 34.46 s, P < 0.05).DiscussionOur findings demonstrated an 18.70% seroprevalence of anti-HEV antibodies among chronically HBV-infected patients in the Hebei Province, with a significantly higher risk of coinfection in older individuals. HBV/HEV coinfection may aggravate liver injury and impair coagulation. These results provide valuable insights into the epidemiology and clinical consequences of HBV/HEV coinfection in this region.